Lyophilised plasma: evaluation of clotting factor activity over 6 days after reconstitution for transfusion. Issue 8 (11th August 2010) - Schoenfeld, Helge; Pruss, Axel; Keller, Mareike; Schuster, Michael; Meinck, Kristian; Neuner, Bruno; von Heymann, Christian
Abstract : Aims: Little is known about long-term stability of clotting factors in dissolved human lyophilised plasma. This study evaluated clotting factor and inhibitor activity in reconstituted lyophilised plasma after storage for up to 6 days at 4°C. Methods: Five samples from different lots of pooled lyophilised plasma (LyoPlas; German Red Cross Blood Transfusion Service West) were reconstituted. The activity of fibrinogen, factor II (FII), FV, FVII, FVIII, FIX, FX, FXI, FXII, FXIII, antithrombin, plasmin inhibitor, von Willebrand factor antigen, free protein S and protein C were determined immediately and at 2, 4, 6, 24, 48, 72, 96, 120 and 144 h after reconstitution. Tests for bacterial contamination were performed after 12, 72 and 144 h from each plasma bottle. Results: Storage at 4°C for 6 h led to a decrease in the activity of FVIII (Δ −14.9%), FIX (Δ −6.9%) and FXI (Δ −6.3%), and an increase in the activity of plasmin inhibitor (Δ +10.2%). Storage for up to 6 days resulted in a further decrease in activity of FVIII (Δ −24.3%), FIX (Δ −13.4%) and FXI (Δ −22.9%), and, additionally, a decrease in the activity of FV (Δ −15.0%), fibrinogen (Δ −6.9%) and plasmin inhibitor (Δ −17.5%). Other factors and inhibitors, with exception of protein C (Δ +8.2%), remained almost unchanged over time. Blood cultures were sterile and showed no bacterial growth. Conclusions: The activity of all measured coagulation factors and inhibitors in a time course of up to 6 days met required quality standards. Further in vivo testing is required to demonstrate safety and efficacy of extended clinical use of refrigerated reconstituted lyophilised plasma.